Implant survival and Biologic complication rates of monolithic zirconia implant-supported fixed complete-arch dental prostheses - alaidrous, May. (Tufts University. Tisch Library., 2025)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Posthodontics.; Advisor: Panos Papaspyridakos.; Committee: Konstantinos Vazouras, Khaled El Rafie, and Matthew Finkelman.; Keyword: Dentistry.